2015
DOI: 10.12693/aphyspola.127.1133
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization and Thermal Properties of Aluminium Titanate/Porcelain Ceramic Matrix Composites

Abstract: Porcelain represents one of the most complex ceramics, formulated from a mix of clay, feldspar and quartz, sintered at temperatures between 1200• C and 1400• C, to form a glass-ceramic composite. Aluminium titanate (Al2TiO5) exhibits extremely good thermal shock resistance and low thermal conductivity, coupled with good chemical resistance in molten metals. In the present work, aluminium titanate/porcelain ceramics composites with dierent percentages of Al2TiO5 was prepared using powder metallurgy techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…However, the measured Young's modulus and Vickers hardness values were higher than the theoretical values predicted for mixtures of Al 2 O 3 and Ti. This is attributed to the presence of TiAl 2 O 5 , which has been shown to be beneficial for improving hardness . The impurity effect of TiAl 2 O 5 on Ti particles such as dissolving small amount of Al and/or oxygen elements was also considered to contribute to the increased Young's modulus and Vickers hardness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the measured Young's modulus and Vickers hardness values were higher than the theoretical values predicted for mixtures of Al 2 O 3 and Ti. This is attributed to the presence of TiAl 2 O 5 , which has been shown to be beneficial for improving hardness . The impurity effect of TiAl 2 O 5 on Ti particles such as dissolving small amount of Al and/or oxygen elements was also considered to contribute to the increased Young's modulus and Vickers hardness.…”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to the presence of TiAl 2 O 5 , which has been shown to be beneficial for improving hardness. 28 The impurity effect of TiAl 2 O 5 on Ti particles such as dissolving small amount of Al and/or oxygen elements was also considered to contribute to the increased Young's modulus and Vickers hardness. 29 The decreased flexural strength of Al 2 O 3 /Ti composites was ascribed to lower flexural strength of Ti than that of Al 2 O 3 .…”
Section: Microstructure and Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the weakened interfacial reaction between Al 2 O 3 and Ti after CeO 2 addition, the increased amount of metallic Ti particles, which could contribute to toughening from ductile fracture, resulted in the higher fracture toughness. In Al 2 O 3 /Ti composite without CeO 2 , interfacial reaction product of TiAl 2 O 5 was generated and these particles fill up grain boundaries and weaken the bonding force, 20,21 which limits the increase in fracture toughness 39 …”
Section: Discussionmentioning
confidence: 99%
“…In Al 2 O 3 /Ti composite without CeO 2 , interfacial reaction product of TiAl 2 O 5 was generated and these particles fill up grain boundaries and weaken the bonding force, 20,21 which limits the increase in fracture toughness. 39 For further investigation, crack propagation behavior is shown in Figure 9. It is found that the toughening mechanisms are mainly ascribed to transgranular fracture and crack deflection [ Figure 9A]) and crack bridging by Ti [ Figure 9B] and elongated CeAl 11 O 18 particles [ Figure 9C].…”
Section: Toughening Mechanismmentioning
confidence: 99%